The Effect of Bilingual Practices on Foreign Language Learning Experiences of International Students in Higher Education - Zuraini, Seruji; Minah, Mohammed Salleh; Noor Aina, Dani (Academy Publication, 2025)
This study investigates the impactful bilingual practices of an instructor teaching a foreign language course (Malay) and their profound effect on the language learning experiences of participants (N > 63) from diverse countries beyond the Southeast Asian region. We gathered valuable insights through comprehensive participant observations and in-depth interviews with the instructor. After five weeks, we administered a questionnaire to evaluate the foreign language learning experiences of international students. Our findings reveal that the instructor implements her bilingual practices into three pivotal themes: the nature of these practices (what), descriptions of their intended purposes (why), and the underlying reasons for their implementation (how). The instructor embraced a flexible bilingual model, employing effective techniques such as code-switching, contextual and linguistic support, personalised adaptations of bilingual practices, and role modelling. The responses from participants indicate remarkable satisfaction with their language learning experiences, averaging an impressive score of 3.85. Moreover, their average exam score of 0.193 corresponds to a large Eta-squared effect size of 19%. This evidence underscores the significant impact of the instructor’s bilingual practices on enhancing participants’ foreign language learning experiences, resulting in meaningful variability in their academic performance. We assert that this research is a pioneer within the context of higher education in Malaysia, as it comprehensively explores international students’ language learning experiences from a truly global perspective. A comparative study of non-Asian and Asian students in the Malay Course could provide valuable insights into language learning experiences across cultures.